Clinical applications of machine learning algorithms: beyond the black box. (12th March 2019) - Watson, David S; Krutzinna, Jenny; Bruce, Ian N; Griffiths, Christopher EM; McInnes, Iain B; Barnes, Michael R; Floridi, Luciano
Abstract : To maximise the clinical benefits of machine learning algorithms, we need to rethink our approach to explanation, argue David Watson and colleagues